2012
DOI: 10.1111/j.1365-2184.2012.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel hydrophilic docetaxel (CQMU‐0519) analogue inhibits proliferation and induces apoptosis in human A549 lung, SKVO3 ovarian and MCF7 breast carcinoma cell lines

Abstract: Novel hydrophilic docetaxel analogue (CQMU-0519) inhibited cell proliferation and enhanced the intrinsic apoptotic pathway in lung and ovarian carcinoma cells, whereas it used the extrinsic one in breast adenocarcinoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…However, it deserves mentioning that these pores have never been observed experimentally [26]. Indirect indication of relevancy of the theory attributed the effect of EMF to the entrance of water molecules in the defects of the membranes can be correlated to the hydrophilic analogue of docetaxel showing increased inhibition of cell proliferation with cell cycle delay at G2/M phases along with induction of apoptosis compared to the original docetaxel in MCF-7 cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, it deserves mentioning that these pores have never been observed experimentally [26]. Indirect indication of relevancy of the theory attributed the effect of EMF to the entrance of water molecules in the defects of the membranes can be correlated to the hydrophilic analogue of docetaxel showing increased inhibition of cell proliferation with cell cycle delay at G2/M phases along with induction of apoptosis compared to the original docetaxel in MCF-7 cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…Initiator and executioner caspases have been found to be activated in many types of cancer cell lines after the application of classical as well as novel taxanes (7,12,27,31,44). Activation of individual caspases seems to be cell type and also applied taxane specific.…”
Section: Figure 4 Effect Of Sb-t-12854 On the Level Of Proteins Of The Bcl-2 Family In Sk-br-3 Mcf-7 And T47d Cells Ie (A) Proapoptotic Pmentioning
confidence: 99%
“…Recently, several groups including ours have reported that caspase-2, a highly conservative protease involved in cell death induction by different stimuli (28), appears to play an important role in taxane-induced cell death (29)(30)(31). Executioner caspase-3, -7 and -6 have also been activated after taxane application in various types of cancer cells (7,12,32). Caspase-3 probably plays the most important role here, while caspase-6 and -7 seem to have minor roles (23,32).…”
mentioning
confidence: 95%
See 2 more Smart Citations